2018
DOI: 10.5005/jp-journals-10030-1217
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of Functional Fibrinogen Assays using TEG and ROTEM in Trauma Patients Enrolled in the FiiRST Trial

Abstract: Introduction:Given the growing use of both thrombelastography (TEG) and rotational thromboelastometry (ROTEM) in trauma and surgery, it is important to determine whether the two are interchangeable, and how comparable they are to Clauss fibrinogen assay and for clinical use. We recently completed a randomized control trial on early fibrinogen in trauma (the FiiRST trial). The object of this analysis was to evaluate the interchangeability and correlations between TEG and ROTEM functional fibrinogen assays in in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…7 Technical specifications and the interpretation of results have been published extensively for each machine. [8][9][10] The ROTEM ® FIBTEM and TEG ® Functional Fibrinogen assays use different platelet inhibitors to measure the clot strength attributable to fibrinogen polymerisation, with results then reported as amplitudes in millimetres. 4 As a result of differences between the ROTEM ® and TEG ® assays, their results are not interchangeable.…”
Section: Accepted 19 November 2023mentioning
confidence: 99%
See 1 more Smart Citation
“…7 Technical specifications and the interpretation of results have been published extensively for each machine. [8][9][10] The ROTEM ® FIBTEM and TEG ® Functional Fibrinogen assays use different platelet inhibitors to measure the clot strength attributable to fibrinogen polymerisation, with results then reported as amplitudes in millimetres. 4 As a result of differences between the ROTEM ® and TEG ® assays, their results are not interchangeable.…”
Section: Accepted 19 November 2023mentioning
confidence: 99%
“…4 It has been shown that functional fibrinogen levels measured by VHAs and the CFA method correlated well in trauma patients. 10,11 Similarly, TEG ® and ROTEM ® indices have previously been highly correlated, although they cannot be used interchangeably. 10 Most data that exist describing the relationships between indices pertain to the timepoint when trauma patients first arrive in the ED, with few data documenting that the consistency of agreement remains constant throughout trauma patients' hospital stay (i.e., over the hours and days after initial haemostatic resuscitation and damage-control surgery).…”
Section: Accepted 19 November 2023mentioning
confidence: 99%
“…This is the reason for the measurement of fibrinogen levels being used as an indicator of pathological conditions. At present, a variety of methods are used to determine the concentration of fibrinogen in blood plasma [11,[14][15][16][17][18][19][20][21][22][23]. Some of them are cheap and simple enough to even be used in field conditions [11,22,23].…”
Section: Introductionmentioning
confidence: 99%